Viscous low Froude number flow interacting with mesoscale orography - Gutiérrez Camacho, Jorge A. (1998)
The interactions of viscuos flow and orography are analysed with particular attention to the generation of vorticity and the shedding of vortices. It is found that at low leves in the flow (one fifth of the orography's height) no vortex shedding takes place, whereas at higher levels such as one-half, and three quarters of the orography's height vortex street are formed. These simulations are performed by means of a three-dimensional. non-hydrostatic, non-linear numerical model. The flow investigated is continuosly stratified.